Liberia's gender-sensitive police reform. Starting from scratch? Improving representation and responsiveness - Laura Bacon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
After its 14-year civil war, Liberia worked with multiple donors and partners to restore security. This paper explores the Liberia National Police's innovative efforts to create a more gender-sensitive police service and describes the international and domestic support it received in doing so. In particular, the paper analyses Liberia National Police's efforts to (1) recruit female police officers and (2) train a specialized unit to address gender-related crimes. Ambitious recruitment efforts brought more women on board, but some critics regarded the related fast-track program as misguided or ineffective. The specialized unit increased awareness about and response to gender-based violence, but was impeded by a broken judicial system. Success factors of both projects included the timing (post-conflict window of opportunity), the context (momentum for gender-sensitive reforms), local ownership a supportive president), and the nature of the aid (problem-driven interventions and iterative learning, vast financial and technical support, including dedicated and continuous support from the United Nations). However, the sustainability of projects' successes remained uncertain, given Liberia's extremely low technical capacity - especially its weak rule of law - as well as certain flaws in the program design.
Keywords: D73; D78; F35; J16; 330; Liberia; police; reform; post-conflict; women; sexual and gender-based violence